Pengaruh Learning Agility, Eksplorasi Kompetensi, dan Training terhadap Kinerja Karyawan melalui Komitmen - Nurul Afni Fauziah; Dewi Puspaningtyas Faeni; Adi Wibowo Noor Fikri (Penerbit Goodwood, 2024)
Purpose: This study aimed to determine whether there is a Relationship Between Learning Agility, Competency Exploration, and Training and Development on Employee Performance mediated by Organizational Commitment at PT. Kaya Raya Turun Temurun (Prestisa).Methodology: The method used in this study was quantitative, and the survey method was used to obtain primary data through a questionnaire. The sampling technique used was a simple random sampling technique with 135 respondents. The data analysis technique uses the outer model and inner model tests with SmartPLS 4.0Results: The study shows that competency exploration affects employee performance, but not significantly, through organizational commitment. Meanwhile, learning agility, competency exploration, and training and development significantly impact employee performance via organizational commitment.Conclusions: Learning agility and training and development have a positive and significant effect on employee performance through organizational commitment, while competency exploration has a positive but insignificant effect. Overall, these three factors affect employee performance, with organizational commitment as an important mediator.Limitations: This study was limited to employees at PT. Kaya Raya Turun Temurun (Prestisa) in 2024. The study focuses only on the relationship between learning agility, competency exploration, and training and development on employee performance mediated by organizational commitment.Contribution: This study is useful for PT. Kaya Raya Turun Temurun (Prestisa) in 2024.